DEVELOPMENT AND CHARACTERIZATION OF GREEN APPLE PEEL EXTRACT BASED NANOPARTICLES - Kum Madhu Kanwar Rathore; Choudhary Suresh (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The main objective of the present work was to prepare green apple peel extract based nano particles by chemical complexation method. Ethanolic extracts of green apple peel were prepared by using Soxhlet apparatus and evaluated for phyto-chemical constituents. Qualitative analysis showed that green apple peel extract showed positive results for alkaloids, tannin and saponins. The percentage moisture content and pH of the extract was found to be 72% and 3.6 respectively. A zeta potential and particle size of prepared nanoparticles was found in the range of -24.6 mV to -35.0 mV and 118.6 nm to 231.7 nm, respectively. These range confirms that obtained particles were in nano range, i.e. <500 nm size. SEM results indicated the formation of nanoparticles and were relatively spherical in shape. Energy dispersive spectrometry (EDS) analysis confirms the presence of AgNPs. Further the study will be extended for anti-microbial and wound healing activities.